TINJAUAN YURIDIS KEBIJAKAN PEMERINTAH DALAM PENANGGULANGAN DAMPAK LUMPUR SIDOARJO BERDASARKAN ILMU PERUNDANG-UNDANGAN (Lex Jurnalica, 2019)
AbstractThe hot mudflow in Porong, Sidoarjo in 2006 resulted in the loss of residences and affected people's livelihoods. To deal with this the government has issued policies in the form of presidential decrees and presidential regulations. The Legislative Study is the initial door for evaluating government policies related to selected legal products. From the initial door, it can be seen the purpose of the government in issuing regulations as the basis for implementing a policy. This paper is structured to gain an in-depth understanding of the accuracy of government choices in determining the types of legislation to implement policies in mitigating the impact of the hot mudflow in Sidoarjo. To obtain the objectives referred to in the foregoing description, in the preparation of this paper using the normative juridical research method with a statute approach. In the science of legislation it is very important to pay attention to the nature of norms in a legal product in the form of regulations which should be general rather than individual or concrete individual. Concrete individual norms contained in Presidential Regulation Number 21 of 2017 concerning Dissolution of the Sidoarjo Mud Handling Agency strengthens the concrete individual norms contained in Presidential Regulation No. 14 of 2007 concerning the Sidoarjo Mud Handling Agency. This means that the Government has chosen the wrong type of legal product to implement its policy. Keywords: Legal Policy, Legislation, legal product AbstrakSemburan lumpur panas di Porong, Sidoarjo pada tahun 2006 berakibat pada hilangnya tempat tinggal dan mata pencaharian warga terdampak. Untuk menangani hal tersebut pemerintah telah mengeluarkan kebijakan-kebijakan dalam bentuk keputusan presiden dan peraturan presiden. Kajian Ilmu perundang-undangan merupakan pintu awal penilaian kebijakan pemerintah dihubungkan dengan produk hukum yang dipilih. Dari pintu awal tersebut dapat diketahui tujuan pemerintah dalam mengeluarkan peraturan sebagai dasar pelaksanaan sebuah kebijakan. Tulisan ini disusun untuk memperoleh pemahaman yang mendalam mengenai ketepatan pilihan pemerintah dalam menentukan jenis peraturan perundang-undangan untuk melaksanakan kebijakan dalam penangggulangan dampak semburan lumpur panas di Sidoarjo. Untuk memperoleh tujuan sebagaimana dimaksud dalam uraian sebelumnya maka dalam penyusunan tulisan ini menggunakan metode penulisan yuridis normatif dengan pendekatan perundang-undangan.Dalam ilmu perundang-undangan sangat penting untuk memperhatikan sifat norma dalam suatu produk hukum. Produk hukum berupa peraturan seharusnya bersifat umum bukan individual apalagi individual konkrit. Norma individual konkrit yang terdapat dalam Peraturan Presiden Nomor 21 Tahun 2017 tentang Pembubaran Badan Penanggulangan Lumpur Sidoarjo menguatkan Norma individual konkrit yang terdapat dalam Peraturan Presiden Nomor 14 tahun 2007 Tentang Badan Penanggulangan Lumpur Sidoarjo. Artinya Pemerintah telah salah dalam memilih jenis produk hukum untuk melaksanakan kebijakannya. Kata Kunci: Kebijakan hukum pemerintah, ilmu perundang-undangan, produk hukum.